1 Setting up a cardiac ct service – pearls and pitfalls. (18th May 2017) - Bassett, Nicholas; Marcus, Neil; Subramanian, Kumar; Maras, Dejan; Kumar, Ganesan; Shukla, Rachana
Abstract : Introduction: CT coronary angiography is being increasingly recognised as an important non-invasive modality for the assessment of coronary artery disease, especially in light of the new NICE guidance. Providing this service in a busy District General Hospital has its challenges and developing the service can be an interesting journey for Radiologists and Cardiologists. Luton and Dunstable University Hospital (L&D) is a large district general hospital in Bedfordshire serving a population of 320, 000. The Cardiac CT service was set up in March 2015. Methods: We retrospectively analysed the first 578 studies performed at the L&D. We reviewed various audits and consequent improvements that were made to the service at various points to increase productivity including Radiographer training and technical support for complex case assessment. We also measured our waiting lists to assess the service demand over time since setting up the service. Results: The service was initially set up as a single session once a week with 2–3 patients per session. This grew steadily over the past two years to two sessions per week with 5–6 patients per session reported by 3 Radiologists and 3 Cardiologists. The waiting list has risen from one week to six since the introduction of new NICE guidelines. We are now hoping to move to a 5 day service. Conclusion: Introducing a relatively high demand service to a busy DGH Radiology department can be difficult. Careful time management, training and planning are required with regular audit of scan quality, time for scanning and reporting.